Layanan Kesehatan Swadaya Masyarakat untuk Lansia - Suharto, Agus; Bahiroh, Siti; Ramadhan, Cahyo Setiadi (Universitas Muhammadiyah Yogyakarta, 2019)
The high number of elderly people in Dagen Hamlets, Pendowoharjo, Bantul requires special highlight, especially regarding the health care. This urgency is due to the fact that elderly people generally have accessibility limitations in addition to the remote location of health facilities. Therefore, health service which is practical and easy-to-reach/access by the elderly people needs to be managed to take place. The society empowerment effort, especially towards elderly people, was conducted step-by-step, involving socializations, trainings, practices, and local health service facility establishment. The success indicator achieved in this empowerment activities is shown by the improvement of people’s awareness, especially the elderly ones, towards the significance of health, health service post visitation intensity, and the development of the non-governmental health service facility.